Infant and young child feeding practices and its associated factors among mothers of under two years children in a western hilly region of Nepal. - Nabin Adhikari; Kiran Acharya; Dipak Prasad Upadhya; Sumita Pathak; Sachin Pokharel; Pranil Man Singh Pradhan (PLoS ONE)
Infant and young child feeding is a key area to improve child survival and promote healthy growth and development. Nepal government has developed and implemented different programs to improve infant and young child feeding practice. However, the practice remains poor and is a major cause of malnutrition in Nepal. This study aims to identify infant and young child feeding practices and its associated factors among mothers of children aged less than two years in western hilly region of Nepal. A descriptive cross-sectional study was carried out among 360 mothers of under two years' children in Syangja district. A semi structural questionnaire was used. Data was entered in EpiData and analyzed using IBM SPSS version 21. Descriptive statistics were used to report the feeding practices and other independent variables. Bivariate and multivariate logistic regression model was used to establish the factors associated with infant and young child feeding practices. The prevalence of breastfeeding, timely initiation of breastfeeding, exclusive breastfeeding, timely initiation of complementary feeding, minimum dietary diversity, minimum meal frequency and minimum acceptable diet (MAD) were 95.6%, 69.2%, 47.6%, 53.3%, 61.5%, 67.3% and 49.9% respectively. Normal delivery (AOR 6.1, 95% CI 1.2-31.3) and higher maternal autonomy (AOR 5.2, 95% CI 1.8-14.6) were significantly associated with exclusive breastfeeding. Similarly, crop production and food security (AOR 3.8, 95% CI 1.9-7.7), maternal knowledge on MAD (AOR 2.5, 95% CI 1.0-6.2) and maternal autonomy (AOR 4.2, 95% CI 2.1-8.4) were significantly associated with minimum acceptable diet. Factors such as maternal education, maternal health services utilization, maternal knowledge, and maternal autonomy were associated with infant and young child feeding practices, which warrants further attention to these factors to reduce malnutrition.